Distribution of Trace Elements, Sr-C Isotopes, and Sedimentary Characteristics as Paleoenvironmental Indicator of the Late Permian Linxi Formation in the Linxi Area, Eastern Inner Mongolia - Linlin Wang; Yongsheng Zhang; Enyuan Xing; Yuan Peng; Dongdong Yu (Journal of Chemistry)
The Late Permian on the periphery of the Songliao Basin, eastern Inner Mongolia, is an important hydrocarbon source rock system. Its sedimentary environment plays an important role in the evaluation of hydrocarbon prospects in the area. Unfortunately, until now, the interpretation of the sedimentary environment of this area has been controversial. We investigated the Late Permian sedimentary environment by studying the sedimentary characteristics and geochemistry. Based on these investigations, we conclude that the Linxi Formation is mainly composed of clastic sediments, interbedded with limestone lenses, with bioherm limestone at the top of the formation. Inner-layer marine fossils (calcium algae, bryozoans, and sponges) and freshwater and blackish water microfossils (bivalves) are all present, indicative of a typical shallow water sedimentary environment with an open and concussion background. In terms of geochemistry, the formation is relatively light rare Earth enriched, with significant positive Eu anomaly, slight positive La and Y anomaly, weak positive Gd anomaly, and lack of Ce anomaly. The average B/Ga ratio of the mudstone is greater than 3.3, and the average Sr/Ba ratio of the limestone is greater than 1.0. The range of the 87Sr/86Sr ratio is from 0.707285 to 0.707953. The range of δ13C values is from −4.0‰ to 2.4‰. The sediment assemblages, rare Earth elements, trace elements, and 87Sr/86Sr and C isotopes of the formation indicate that the Linxi Formation formed in a marine sedimentary environment and occasional marine-terrestrial transitional facies. The formation can be further divided into littoral facies, neritic facies, bathyal facies, and delta front.